Posttraumatic Vertigo and Dizziness - Fife, Terry D.; Giza, Christopher (Seminars in Neurology, 2013)
Dizziness and vertigo are common symptoms following minor head trauma. Although these symptoms resolve within a few weeks in many patients, in some the symptoms may last much longer and impede ability to return to work and full functioning. Causes of persisting or recurrent dizziness may include benign paroxysmal positional vertigo, so-called labyrinthine concussion, unilateral vestibular nerve injury or damage to the utricle or saccule, perilymphatic fistula, or less commonly traumatic endolymphatic hydrops. Some dizziness after head trauma is due to nonlabyrinthine causes that may be related to structural or microstructural central nervous system injury or to more complicated interactions between migraine, generalized anxiety, and issues related to patients self-perception, predisposing psychological states, and environmental and stress-related factors. In this article, the authors review both the inner ear causes of dizziness after concussion and also the current understanding of chronic postconcussive dizziness when no peripheral vestibular cause can be identified.
Keywords: postconcussive syndrome; postconcussive dizziness; vertigo; traumatic brain injury